2022
DOI: 10.3389/fenrg.2021.784082
|View full text |Cite
|
Sign up to set email alerts
|

Short-Lived Interfaces in Energy Materials

Abstract: The kinetics of most chemical energy storage/conversion systems depend on the mass transport through matter, which is rate-limited by various kinetic barriers. The distinction of the barriers by static and dynamic interfaces helps in reducing their impact and therefore enhancing the overall kinetics. The concept is introduced along examples of static and dynamic interfaces in hydrogen storage, thermal energy storage in absorptive media, and electrochemical water splitting and CO2 reduction. In addition to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…The second difficulty is that hydrogen can be detected and quantified by very few in situ methods only. [47][48][49] Terreni et al 32,50 demonstrated the use of neutron radiography for hydrogen detection in catalysts. Neutron imaging is element-specific for hydrogen and compatible under the harsh conditions in catalysis, but lacks chemical selectivity.…”
Section: Methodsmentioning
confidence: 99%
“…The second difficulty is that hydrogen can be detected and quantified by very few in situ methods only. [47][48][49] Terreni et al 32,50 demonstrated the use of neutron radiography for hydrogen detection in catalysts. Neutron imaging is element-specific for hydrogen and compatible under the harsh conditions in catalysis, but lacks chemical selectivity.…”
Section: Methodsmentioning
confidence: 99%
“…The knowledge gap arises from the same uncertainties described above and owing to the fact that current experimental methods provide information only on either the time-resolved but spatially averaged concentration in a metal (hydride) during the sorption process, or vice versa. Available methods usually rely on sophisticated analytical setups [3,18] such as electron microscopy [19,20], elastic recoil distribution analysis [21], N15-nuclear resonance analysis [22e24] etc., which are difficult to convert into an operando method.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Hydrogen sorption kinetics may also be surface limited in a number of metal hydrides for hydrogen storage. [33,[51][52][53] Some additives with low dissociation barriers including Pd attached to the metal-hydride surface are known. [52] This study may provide a different way at interpreting the experimentally derived activation energies of such systems.…”
mentioning
confidence: 99%